Photoadsorption and reaction mechanism of periwinkle shell ash in the removal of hazardous dye. Issue 3 (6th March 2023) - Nkwoada, Amarachi; Onyedika, Gerald; Oguzie, Emeka; Ogwuegbu, Martin
Abstract: Combined adsorption and photocatalysis synergy was explored in this research because the porosity of activated carbon and hydroxyl radicals' generation are the main drivers of the adsorption and photodecomposition efficiency of dyes. In this study, periwinkle shell ash (PSA) activated at 800 °C was used for the adsorption of toxic crystal violet (CRV) dyes. The PSA was characterized by scanning electron microscope, Fourier transform infrared spectroscopy, thermogravimetric analysis, Brunauer–Emmett–Teller surface area analysis, and X-ray diffraction. Findings showed that CRV adsorption was dependent on the dosage, pH, contact time, and initial concentration. The adsorption capacity was 46.82 at pH (9) for CRV, dosage amount of 0.2 g/L, and an adsorbate concentration of 70 mg/L. Pseudo-second order gave a perfect fitting-chemisorption mechanism with values >0.98 ( R 2 ). Maximum photodegradation (93–98%) was achieved when the catalyst dosage increased to 0.75 g. Thermodynamics confirmed a spontaneous/exothermic process. The photocatalysis process confirmed that the combined process was effective and determined to be the rate-determining step by Langmuir–Hinshelwood. The study concluded that PSA was an efficient adsorbent, and TiO2 was a key factor in the reaction mechanism and recommended for potential synthesis of membrane substrates, high performance, efficiency, and cost reduction. HIGHLIGHTS: The pore width improved from 2.92 to 3.82 nm, and the surface area went from 628 to 831 m 2 /g. Two major regions of adsorption were confirmed by intra-particle diffusion and the Boyd model, proving the existence of additional rate-determining processes. The maximum adsorption capacity, which was higher than earlier studies on periwinkle shells, was 46.82 mg/g. Chemisorption mechanism was shown to be the cause of the adsorption by pseudo-second-order kinetics. Maximum photodegradation was achieved with a 99.9% efficiency at a catalyst dosage of 0.75 g, owing to an increase in hydroxyl radicals. Graphical Abstract